A new sintering approach to ceramics at low temperature from Ba(Zr x Ti1-x )O3 nanoparticles doped by ZnO - Rui Guo; Jianquan Qi; Jiali Luo; Xiaoyu Dong; Longtu Li (Journal of Advanced Ceramics, 2016)
Abstract The sintering temperature decreases theoretically with the grain size of the ceramic powders, but it is not always right for fine grain sized nanopowders due to the inevitable agglomerations, and thus pores are hard to eliminate thoroughly during sintering. To overcome this difficulty, a new approach is designed to sintering ceramics at low temperature from nanoparticles. In this scheme, excessive dopants, such as ZnO, are synthesized into the nanoparticles, and they would be liberated again on the surfaces of the grains at high temperature as sintering aids homogenously to promote densification. Here, we compared the ceramic sintering of ZnO-doped barium zirconate titanate (BaZr x Ti1-x O3, BZT) nanoparticles with BZT nanoparticles using ZnO as additive at 1150 °C. Both kinds of nanoparticles were directly synthesized by the same process at room temperature and yielded the same initial grain size of ~10 nm. The dense BZT ceramic with relative density of 99% was fabricated from the 2 mol% ZnO-doped nanoparticles. On the other hand, the porous BZT ceramic with density of 78% was obtained from nanoparticles with 2 mol% ZnO as additive. Therefore, our strategy to ceramic sintering at low temperature from nanoparticles was confirmed.